Effects of ashwagandha (withania somnifera) supplementation on special endurance and response time of elite wrestlers - Gierczuk, D.; Jówko, E.; Zawadzki, W.; Cieslinski, I.; Sadowski, J. (The Journal of Strength and Conditioning Research, 2025)
The aim of this study was to determine the effect of ashwagandha supplementation on special endurance and response time of highly qualified wrestlers participating in a structured sports training process (preparatory period). In the randomized, double-blind manner, national team wrestlers received either placebo or ashwagandha extract (600 mg·d-1) for 8 weeks. Twice during the 8-week study period: Pre-intervention (term I) and post-intervention (term II), special endurance (using the dummy suplex throw test), and response time to a stimulus (decision test using the Vienna Test System) were assessed. In term II, as compared with term I, an increase in special endurance (total number of throws) occurred in both groups (main effect of time: p = 0.000001, post hoc p < 0.001). In addition, both groups experienced favorable changes in the number of correct reactions (main time effect: p = 0.002; post hoc p < 0.05) and the time of choice reaction (main time effect: p = 0.0001, post hoc p < 0.01). By contrast, no main effect of group or time × group interaction was found in the parameters studied (p > 0.05). In conclusion, in highly qualified wrestlers performing a training program during the preparatory period, 8-week supplementation with ashwagandha at a dose of 600 mg per day does not appear to offer additional benefits in terms of an increase in special endurance and an improvement in response time to stimuli beyond those observed as a result of training. Further research is needed using either longer periods of ashwagandha supplementation or in the search for other dietary supplements to support the training process of wrestlers.